Public Private Partnerships in International Construction Learning from case studies - Chan, Albert P.C (Taylor & Francis, 2013)
Over the last ten years public private partnerships have become ever more popular worldwide, expanding the body of experience among construction professionals, government agencies, and industry. In these economically challenging times, PPP has emerged as a crucial framework for providing infrastructure, and also to boost construction industry activity, while shielding the taxpayer from some of the cost. Understanding the lessons learnt is essential to ensuring the success of future projects, and this timely book will prepare the reader to do just that. Starting by defining PPP itself, part one is designed to help the novice to get to grips with the basics of this topic. Part two tackles the practicalities of PPPs, including successful implementation, managing the risks involved, and how to assess the suitability of a project for the PPP route. Part three presents detailed case studies from Asia, Africa, and Australia to illustrate how PPPs should be managed, how problems emerge, and how PPPs can differ across the world. Drawing on extensive internationally conducted research, from both industry and academia, the authors have written the essential PPP guide. Taking into consideration the perspectives of those in the public sector and the private sector, as well as built environment professionals, it is essential reading for anyone preparing to work on public private partnerships in construction.